2012
DOI: 10.1038/ng.1046
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of common variants associated with low TSH levels and thyroid cancer risk

Abstract: To search for sequence variants conferring risk of nonmedullary thyroid cancer, we focused our analysis on 22 SNPs with a P < 5 × 10−8 in a genome-wide association study on levels of thyroid stimulating hormone (TSH) in 27,758 Icelanders. Of those, rs965513 has previously been shown to associate with thyroid cancer. The remaining 21 SNPs were genotyped in 561 Icelandic individuals with thyroid cancer (cases) and up to 40,013 controls. Variants suggestively associated with thyroid cancer (P < 0.05) were genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
264
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 224 publications
(292 citation statements)
references
References 30 publications
25
264
2
1
Order By: Relevance
“…So far, exposure to ionizing radiation is the only well established risk factor for thyroid cancer, especially when it occurs in early stages of life (Papadopoulou et al, 2009). However, there are evidences that many gene polymorphisms including DNA repair genes influence on thyroid cancer susceptibility (Gudmundsson et al, 2012(Gudmundsson et al, ,2001Marsin et al, 2003). There have been more than 300 validated SNPs (single nucleotide polymorphism) in the XRCC1 gene, however, only three SNPs have been extensively studied including Arg194Trp, Arg280His and Arg399Gln.…”
Section: Introductionmentioning
confidence: 99%
“…So far, exposure to ionizing radiation is the only well established risk factor for thyroid cancer, especially when it occurs in early stages of life (Papadopoulou et al, 2009). However, there are evidences that many gene polymorphisms including DNA repair genes influence on thyroid cancer susceptibility (Gudmundsson et al, 2012(Gudmundsson et al, ,2001Marsin et al, 2003). There have been more than 300 validated SNPs (single nucleotide polymorphism) in the XRCC1 gene, however, only three SNPs have been extensively studied including Arg194Trp, Arg280His and Arg399Gln.…”
Section: Introductionmentioning
confidence: 99%
“…Such genes are not amenable to detection by linkage analysis but can be found by association analysis in large datasets (10). Until now, three genome-wide association studies (GWAS) have addressed the predisposition to PTC (11)(12)(13). Gudmundsson et al (11) studied Icelandic PTC patients and controls, followed by validation in Spanish and US cases and controls.…”
mentioning
confidence: 99%
“…We studied the predictive value of the five markers detected in two recently published GWASs (22,23). We found that the combined use of the genotypes of these markers shows definite promise as a predictive tool, but that more markers are probably needed before genotyping of markers for PTC can become a routinely applied method in clinical practice.…”
mentioning
confidence: 99%